Impact of soil-applied organic manures and organic foliar sprays on growth, productivity and economics of summer sesame (Sesamum indicum L.): IMPACT OF SOIL-APPLIED ORGANIC MANURES AND ORGANIC FOLIAR SPRAYS ON SUMMER SESAME - KESHAV; G KRISHNA REDDY; K NAVYA JYOTHI; P LAVANYA KUMARI; A SAGAR; G ASHWINI (Journal of Oilseeds Research, 2026)
To investigate the impact of organic manures and organic foliar sprays on the growth, productivity, and economics of summer sesame (Sesamum indicum L.), a split-plot experiment was conducted during the summer season of 2023. The treatments comprised organic manures, viz., farmyard manure, poultry manure, and vermicompost, assigned to the main plots, and organic foliar sprays, viz., seaweed extract, egg amino acid, humic acid, jeevamrith, fish amino acid, and panchgavya, assigned to the subplots, with three replications. The application of poultry manure along with foliar spraying of seaweed extract @ 0.3% at 20, 40, and 60 DAS resulted in greater plant height, leaf area, dry matter accumulation, SPAD readings, yield attributes, seed yield (623 kg/ha), and stalk yield (1247 kg/ha). However, significantly higher net returns and a benefit-cost ratio were achieved with the application of poultry manure combined with foliar spraying of jeevamrith @ 3.0% at 20, 40, and 60 DAS.